Motivated memory in economics: A review - Andrea Amelio; Florian Zimmermann (Games, 2023)
Motivated reasoning refers to the idea that people hold certain beliefs about themselves or the world due to their desire to do so, rather than striving for accuracy. This type of belief formation can lead to overconfidence and polarization, as well as facilitate immoral behavior at both the individual and collective levels. One of the supply-side mechanisms for motivated reasoning is motivated memory, or the selective retrieval of past experiences or information based on self-serving criteria. In this article, we review the still young economics literature on motivated memory. Summarizing both theoretical and empirical work, we highlight the key results this literature has produced. We also discuss open questions and potentially exciting avenues for future research in this area.
Keywords: 330; motivated reasoning; memory; beliefs; experiments